Confronting Dystopia: The Power of Cognition in Neal Stephenson's Snow Crash and The Diamond Age. Issue 1 (April 2017) - Lewis, Jonathan
Abstract : Neal Stephenson's novels are typically labeled "dystopic, " but such marketing offers little use-value for understanding his significant contributions to contemporary science fiction. His work breaks with traditional definitions of dystopic fictions at nearly every turn by offering scenarios where human creativity and cognition offer real hope against such potential disasters. Snow Crash and The Diamond Age 's protagonists build cognitive responses to the dystopic wastelands they inhabit, but Stephenson's terrifying novelistic premises and conceptions for future technologies and their myriad uses should be properly characterized as constructive and optimistic Jamesonian anti-utopias. Stephenson's work certainly does not suggest that innovation alone can be our panacea, but he does put forward throughout his work that cognition just might.